ỨNG DỤNG GIS VÀ TƯ LIỆU VIỄN THÁM ĐÁNH GIÁ BIẾN ĐỘNG LỚP PHỦ RỪNG TẠI VÙNG ĐỆM VƯỜN QUỐC GIA CÁT TIÊN THUỘC ĐỊA PHẬN HUYỆN TÂN PHÚ, TỈNH ĐỒNG NAI - Nguyễn, Trung Đức; Nguyễn, Thị Vân; Trương, Thị Ngân; Đinh, Tiến Hậu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
APPLICATION OF GIS AND REMOTE SENSING DATA FOR ASSESSMENT OF FOREST COVER CHANGE IN THE BUFFER ZONE OF CAT TIEN NATIONAL PARK IN TAN PHU DISTRICT, DONG NAI PROVINCE The Cat Tien National Park in the South of Vietnam represents a protected ecological area, it is located in tropical rainforest zone. For assessment of forest cover change in three buffer zones of Cat Tien National Park, namely Nam Cat Tien, Nui Tuong and Phu An at Tan Phu district, satellite images (Landsat 5 TM and Landsat 8 OLI) take in 1990, 2000, 2010 and 2020 were used. Land use/land cover were classified by 5 categories using maximum likelihood classifier (MLC) method, result of constructing a key for image classification showed that images without reference data for classification have over 83.50% of map accuracies. After classification, differentiation of forest land use/landcover was analysied in each year. Deforestation and agricultural area reduction took place in 1990 - 2020 period. Besides, study has quantified changes in forest cover during periods: 1990 - 2000, 2000 - 2010 and 2010 - 2020. As a result, findings show that the extents of forest cover have decreased from 5522.22 ha to 2620.98 ha during the period of 1990 - 2020. Maps of forest status as well as changes in forests can be used for forest resource management activities under the Cat Tien National Park management.